God"s servant working for your own good: Notes from modern South Africa on Calvin"s commentary on Romans 13: 1-7 and the state - Strauss, P. J. (Hervormde teologiese studies, 1998)
This article aims at demonstrating that Calvin's grasp of the message of Romans 13 in its reference to the state is highly relevant for the present South Africa. This includes the belief that the authority of rulers is ordained by God, be it that of a just or an unjust government, and that their right to govern should therefore be respected; that government should maintain a public order of justice and peace within which people can serve God in all spheres of life; that state authorities should use the sword and even the death penalty when needed, and not shy away from this God-given responsibility; that a society in which crime threatens to create chaos needs stronger measures of punishment; and that rebellion against the government or disruption of public life should be resorted to only as an ultimate means and when carefully considered as in the general interest.